Prolegómenos para entender la regulación de la calidad en la ens eñanza universitaria - Chang Chuyes, Guíllermo (2019)
This work wants to establish the bases to understand the quality and its application to theuniversities. Therefore, in a first part we analyze the term quality, to discover its meaning.Then it is exposed how the companies and the State look for the quality in its activities,and how the State tries to regulate it. In the second part, we analyze the structure of theuniversity in Peruvian law, how its quality should be and if the state can regulate it.